Safeguarding Justice Seekers: Institutional Reforms and Public Engagement in Indonesia’s Administrative Law System - Asmuni, Asmuni (Universitas Muhammadiyah Yogyakarta, 2025)
Legal protection for justice seekers can be achieved through the good faith of the state administrative agency or official responsible for executing the state administrative court's decision, coupled with active community oversight of the implementation process. Indonesia requires an executive institution to implement PTUN (Peradilan Tata Usaha Negara) execution, ensuring that legal enforcement operates more efficiently, particularly within the realm of state administrative justice. This research aims to reveal and analyze how legal protection for justice seekers is implemented through state administrative courts and what steps can be taken so that legal protection can be binding. The method applied in this research is a statutory approach, a concept approach, and testing it with case studies of several cases of the State Administrative Court in Indonesia. This study found that a comprehensive approach encompassing good faith implementation, community involvement, establishment of executive institutions, capacity building, training initiatives, and public awareness campaigns is essential for safeguarding legal protection within state administrative justice systems. This collective effort aims to ensure the effective implementation of administrative court decisions, uphold the rule of Law, and protect the rights of justice seekers in Indonesia